Plasmacytoid Dendritic Cells: From Heart to Vessels - Sorrentino, Rosalinda (Hindawi Publishing Corporation, 2010)
Cardiovascular diseases, formerly only attributed to the alterations of the stromal component, are now recognized as immune-based pathologies. Plasmacytoid Dendritic Cells (pDCs) are important immune orchestrators in heart and vessels. They highly produce IFN type I that promote the polarization of T cells towards a Th1 phenotype; however, pDCs can also participate to suppressive networks via the recruitment of T regulatory cells that downmodulate proinflammatory responses. pDCs populate the vessel wall layers during pathological conditions, such as atherosclerosis. It is thus clear that a better identification of pDCs activity in cardiovascular diseases can not only elucidate pathological mechanisms but also lead to new therapeutic approaches.